Balanced Skills and the City: An Analysis of the Relationship between Entrepreneurial Skill Balance, Thickness, and Innovation. (14th July 2015) - Bublitz, Elisabeth; Fritsch, Michael; Wyrwich, Michael
Abstract Entrepreneurs are assumed to be multiskilled, covering a number of skills and achieving in each skill a level as high as possible. Being such a jack‐of‐all‐trades increases the probability of running an entrepreneurial venture successfully, but what happens to the jack‐of‐few‐trades who lacks sufficient skills? This article investigates a possible compensation mechanism between balanced skills and cities and how this compensatory measure relates to performance. Specifically, we test and find support for the idea put forward by Helsley and Strange that high market thickness, such as that found in cities, can compensate for a lack of entrepreneurial skill balance. The results indicate that entrepreneurs with low skill balance benefit more from being located in cities than their counterparts with high skill balance. Innovative firms do not differ from other businesses in this respect.